In vitro Cytotoxicity and Pharmacokinetic Evaluation of Pharmacological Ascorbate in Dogs - Musser, Margaret L.; Mahaffey, Alyssa L.; Fath, Melissa A.; Buettner, Garry R.; Wagner, Brett A.; Schneider, Benjamin K.; Seo, Yeon-Jung; Mochel, Jonathan P.; Johannes, Chad M. (Frontiers in Veterinary Science, 2019)
Background: High-dose, pharmacological ascorbate (P-AscH−) is preferentially cytotoxic to human cancer cells in vitro. Investigations on the efficacy of P-AscH− as an adjuvant treatment for multiple human cancers are on-going, but has yet to be formally investigated in dogs. The primary objectives of this study were to determine the pharmacokinetic (PK) profile of P-AscH− in healthy Beagle dogs and the effects of P-AscH− on canine osteosarcoma cells in vitro. Methods: Eight purpose-bred, healthy, spayed female Beagle dogs, between 20 and 21 months old, and 8–10 kg were administered two doses of P-AscH− (550 or 2,200 mg/kg) via intravenous infusion over 6 h, on separate days. Plasma ascorbate concentrations were measured at 12 time points during and after infusion for PK analysis using nonlinear mixed-effects (NLME) and non-compartmental analysis (NCA). Clonogenic assays were performed on 2 canine osteosarcoma cell lines (D-17 and OSCA-8) and canine primary dermal fibroblasts after exposure to high concentrations of ascorbate (75 pmoles/cell). Results: Plasma ascorbate levels in the dogs peaked at approximately 10 mM following 2,200 mg/kg and returned to baseline 6–8 h after dosing. Minor adverse effects were seen in two dogs. Ascorbate (75 pmoles/cell) significantly decreased survival in both the osteosarcoma cell lines (D-17 63% SD 0.010, P = 0.005; OSCA-8 50% SD 0.086, P = 0.026), compared to normal fibroblasts (27% SD 0.056). Conclusions: Pharmacological ascorbate is preferentially cytotoxic to canine-derived cancer cells. High levels of ascorbate can be safely administered to dogs. Further studies are needed to determine the effects of P-AscH− on canine patients.